Waste-to-Energy Potential Using Municipal Solid Waste as One Implementation of Jakarta Smart City - Muhammad Rayhan Syahida Ramadhan; Muhammad Ikhsan; Ridha Muhlita Putra; Joni Welman Simatupang; Sealtial Mau; Emil Robert Kaburuan (Jurnal Serambi Engineering, 2021)
The background of this research is the escalation of DKI Jakarta’s residence which lead to the other two impacting factors, the use of electricity that increase to 5.8% in 2019 and the municipal waste escalation. The objective of this research is to find potential electrical energy that can be produced from waste-to-energy (WTE) technology of IWMS (Integrated Waste Management Site) Bantargebang (Bekasi), where most of the waste come from the people of DKI Jakarta. Furthermore, with the application of WTE, there is also a potential from the smart city implementation in DKI Jakarta. By using the mathematical model and secondary data gathering from the government of DKI Jakarta, we found that the potential of electrical energy that can be produced can reach 8.6 GWh/day, which contributed up to 9% to from the energy distributed to DKI Jakarta. Moreover, by applying WTE, there is also a potential of implementing other indicators of smart city that has been propagated by the government of DKI Jakarta.